Krajobraz z rekwizytem w tle - Krajewska, Anna (Przestrzenie Teorii, 2025)
This article introduces the idea of a landscape with a prop in the background, bridging the reflections on two main themes explored in previous issues: conceptualizing landscape research as a new transdiscipline, and the prop as an intertwining of object, word, and body. This relational approach to a landscape that “absorbs” the “other” justifies synthesising reflections on space with the role of the prop